Relationship between the Schumann resonance parameters and the temperature on the African continent - Paznukhov, A. V.; Yampolski, Yu. M.; Nickolaenko, A. P.; Koloskov, A. V. (Ukrainian Antarctic Journal, 2017)
Main objective of the study: сorrelation study of long-term seasonal variations of the intensity of the global electromagnetic (Schumann) resonance in the Earth-ionosphere cavity and the air temperature and in African center of the global thunderstorm activity. Methods: the correlation analysis of the time series was used. By using the 13-year data (from 2002 to 2015 years) of monitoring the natural ELF noise at the Ukrainian Antarctic Akademik Vernadsky station, the seasonal variations in the intensity of the first Schumann resonance mode were derived, driven by the lightning activity in the African thunderstorm center. The average air temperature of the African continent over the same period was estimated from the data collected by the global network of meteorological stations. The area of maximum thunderstorm activity in Africa was approximated by a simple geometric figure. The correction was made for the source distance (the lightning discharges) when estimating the power of the first resonant maximum in the ELF signal. A stable relationship between the air temperature and the thunderstorm activity at the African continent was established as a result of correlation processing of seasonal variations in the air temperature and the field intensity. Results: the one month lag between the annual maximum resonance intensity was found relative the maximum of air temperature, relevant to the retard in the formation of thunderstorms during transition from the dry to the rainy seasons in Africa. The cross-correlation coefficient increases from 0.58 (without compensation) to the 0.76 value (delay compensated) when this delay is accounted for by the relevant shift of the temperature variations. Conclusions: the developed technique can be used for finding the connection between the lightning activity of other thunderstorm centers and the corresponding regional temperature regimes. Such an approach might be used in the developing concept of Schumann resonance records as a “global thermometer”.